WHY DOES MUZAKKI PAY ZAKAT THROUGH BAITUL MAAL INSTITUTION? - Elyska Mentari; Suriani Suriani (Syiah Kuala University, 2021)
Abstract Islamic economic philanthropy through zakat is a means of distributing income from the rich to the poor. The decision of muzakki to pay zakah via zakat institution contributes to equal income distribution within an economy. Thus, it crucial to determine the factors causing muzakki to pay zakah via zakat institution. On this basis, this study intends to examine the effect of transparency, motivation, culture, and reputation on the decision of Muzakki to pay the zakat at the baitu maal institution. The method of analysis used in this research is a binary logit regression model. The sampling technique was purposive sampling with as many as 66 respondents. The results showed that transparency, motivation, culture, and reputation had a positive and significant effect on the decision of Muzakki to pay zakat at the baitu maal institution. To increase the interest of muzakki to pay zakat through the baitu maal institution, muzakki needs to be motivated to obey in paying zakat. The baitu maal institution is required to improve its reputation through optimizing service quality.